S51 Patient pathway mapping of uk referrals to the national pulmonary endarterectomy mdt (june 2015 – may 2016). (15th November 2017) - Bunclark, K; Abraham, N; Almeida, L Amaral; Cannon, J; Clare, S; Doughty, N; Dunning, J; Ng, C; Newnham, M; Ponnaberanam, A; Ruggiero, A; Screaton, N; et al.
Abstract : Introduction: Pulmonary endarterectomy (PEA) is the treatment of choice for Chronic Thromboembolic Pulmonary Hypertension (CTEPH) and can be offered to selected patients with Chronic Thromboembolic Disease without pulmonary hypertension (CTED). Our aim was to map the pathway of UK patients referred to the National PEA MDT and their onwards management. Methods: All consecutive individuals referred to the National PEA MDT at Papworth Hospital between June 2015 and May 2016 were included. Patients were divided into CTEPH/CTED groups and their pathways followed until July 2017. Results: Of the 316 referrals to the PEA MDT there were 246 cases of CTEPH, 46 of CTED and 24 with alternate diagnoses. Age range of referrals was 22–88 years (mean 59 years). 51% were male. The majority of CTEPH cases had technically operable disease (n=200, 81%) with 130 proceeding to PEA (65%). 53% of all CTEPH cases were operated on (figure 1 ). Median time from first MDT discussion to PEA was 230 days with a median surgical waiting list time of 115 days. 11 patients required ongoing targeted therapy post-operatively. Of the 70 individuals with an operable disease distribution who did not proceed to PEA, 34 patients chose to decline surgery and 36 were rejected by the surgical team due to co-morbid conditions (n=28) or limited symptoms (n=8). Two patients with distal CTEPH underwent Balloon Pulmonary Angioplasty (BPA). Remaining patients were medically managed with targeted therapy. Of CTED cases, 28 (61%) had an operable disease distribution with 8 (29%) proceeding to PEA. 17% of total CTED referrals were operated on. Conclusion: This patient pathway mapping is the first undertaken for any national CTEPH/CTED cohort. The majority of UK CTEPH cases suitable for PEA are operated on (65%). The duration of time between MDT referral and PEA is reflective of disease complexity and decision-making process. We observe a group of highly selected individuals with Chronic Thromboembolic Disease (CTED) without pulmonary hypertension who undergo PEA after careful consideration of their symptoms and operative risk.